(untitled) (Research, Society and Development, 2020)
Objective: This study is a literature review aimed at synthesizing information regarding the relationship between body posture, gait biomechanics, and the use of sensory insoles, as well as contributing to the investigations on this topic. Methodology: We have collected the research data from the databases Science Direct, MEDLINE/PubMed, Web of Science and Scielo. We used the following descriptors in the search for the articles: body posture, running, injury, plantar pressure, sensors, and sensory insoles; we have also associated these terms with one another in our search. Results: We have selected the articles that contained literature reviews, treatment, or on-site surveys, published up to 2020. This review has identified the existence of several commercially available pressure sensors, with technologies such as capacitive, resistive, piezoelectric, and piezoresistive sensors. This study has also identified several advantages in the use of the insole technology: improvements in balance and speed rates in the anteroposterior region; redistribution of plantar pressure during walking for diabetic patients; alteration of the pressure over time relationship throughout the entire plantar region. Conclusion: The progress obtained by the use of these sensors over the past few years has been motivating researchers to aim for improvements in its performance and practicality, allowing for its use in diagnosing balance disorders, which can be related to body posture and gait biomechanics.